Scarce Occurrence of Calcification in Human Sinoatrial Nodal Arteries in Old Age - Yoshiyuki Tohno (2018)
© 2017, Springer Science+Business Media, LLC. To elucidate age-related changes of the sinoatrial (sinuatrial) nodal (SAN) artery, the authors investigated age-related changes of elements in the SAN artery by direct chemical analysis. In addition, the effects of different arterial origins, arterial sizes, and genders on element accumulation were investigated in the SAN artery. Fifty-nine formalin-fixed adult Thai hearts were dissected, and the following three types of the SAN artery were found: The first type was a single SAN artery arising from the right coronary artery (RCA). The second type was a single SAN artery arising from the proximal segment of the left circumflex artery (LCX). The third type was dual SAN artery arising from both the RCA and the LCX. For element analysis, both 41 single SAN arteries arising from the RCA and the LCX and 18 larger branches of dual SAN artery were used. After the arteries were incinerated with nitric acid and perchloric acid, element contents were determined by inductively coupled plasma-atomic emission spectrometry. It was found that seven element contents such as Ca, P, S, Mg, Zn, Fe, and Na did not change significantly in the SAN arteries with aging. Regarding the relationships among seven elements in the SAN arteries, extremely significant direct correlations were found among P, S, Mg, and Fe contents with one exception. However, no significant correlations were found between Ca and either P or Mg contents in the SAN arteries. To examine an effect of the different arterial origins on element accumulation, the SAN arteries were separated into the RCA and the LCX groups by the arterial origin and age-related changes of element contents were compared between two groups. It was found that there were no significant differences between the RCA and the LCX groups in age-related changes of Ca and P contents. No gender differences were found in age-related changes of Ca and P contents in the SAN arteries. To elucidate whether calcification occurred in the SAN arteries in old age, both the mass ratios of Ca/P and Mg/Ca were estimated in the SAN arteries. The mass ratio of Ca/P increased progressively in the SAN arteries with Ca increase, being not constant. The mass ratio of Mg/Ca decreased gradually in the SAN arteries with Ca increase, but the average mass ratio of Mg/Ca was very high, being 49.4 ± 16.5%. These results indicated that calcification scarcely occurred in the SAN arteries in old age, independently of the arterial origin and gender.